Assessment of the Effectiveness of Ethical Corporate Governance in Corporate Decision-Making: A Grounded Theory Approach - Nwanji, Tony Ikechukwu; Howell, Kerry E.; Faye, Sainey; Agba, Dominic Z.; Adewara, Sunday O.; Lawal, Adedoyin Ishola; Otekunrin, Adegbola Olubukola; Awonusi, Frank D.; Eluyela, Damilola Felix (Archives of Business Research, 2019)
The article focused on the effectiveness of ethical corporate governance in decision making by the board of directors of top listed companies. Through the application of grounded theory approach in analysing data collected via the survey questionnaire, a substantive theory of ethical corporate governance is developed. The substantive theory developed is based on the shareholdership model of empowerment to create wealth and stakeholdership model of expectation to shared values. In term of ethical corporate governance, through organisations code of conduct and corporate social responsibility policies, companies can reach out to their broader stakeholdership groups through engagement with stakeholders. Such engagement is ongoing with shareholdership groups through boards’ accountability to shareholders — the finding from this study further our understanding of ethical corporate governance issues.